Editorial N. 58 june 2024 - Equipo Editorial (2024)
The team at Revista San Gregorio is pleased to welcome you to our 58th edition, a milestone that reflects our ongoing commitment to regularity and excellence in scientific publishing. We take pride in maintaining our presence in renowned databases such as Clarivate Analytics (Emerging Sources Citation Index), Latindex (Methodology 2.0), SciELO-Ecuador, DOAJ, REDIB, Dialnet, among others, ensuring the visibility and impact of our contributions to the scientific field.